ATOMIC NUCLEUS AND ITS PHYSICAL PROPERTIES (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article provides an in-depth exploration of the physical properties of the atomic nucleus, including its structure, composition, and interactions. It covers key concepts in nuclear physics, examines relevant literature, discusses methodologies used in nuclear research, presents notable findings, and concludes with implications and suggestions for further study.